Harmful Effects on Oryzaephilus surinamensis (L.) and Tribolium castaneum by food grade antioxidants and their formulations in Peanut Kernel - García, Daiana (2017)
The aim of this study was to investigate effect of 2(3)-tert-butyl-4hydroxyanisole (BHA) and 2,6-di(tert-butyl)-p-cresol (BHT) and theirformulations on mortality, body weight and total protein content of Oryzaephilussurinamensis (L.) and Tribolium castaneum, Herbst; two natural pest of storedpeanut. The effect of free BHA and BHT and their formulations (F-BHA andF-BHT) at dose range to 10 from 45 mM, in peanut kernel was evaluated. BHAand BHT free antioxidant showed significant mortality percentages upper than80%. Besides, microencapsulated antioxidants at 20 and 30 mM significantlyaffected the survival of insect populations after 45 days of exposure. BHA andBHT formulation showed insecticidal activity of 100 and 70%, respectively.Insect weight was significantly affected by all studied treatments and the majoreffect for O. surinamensis was produced by time especially with the application of BHA follow by F-BHA and F-BHT. Body mass weight of T. castaneum showedthe highest reduction after application of F-BHA, followed F-BHT, BHT andBHA. Total protein content of insects also was affected by both free antioxidants and formulation treatments. Formulations preserved insecticidal effectiveness of antioxidants and extended their effect for up to 45 days which could act as new strategies to control these insect pests. Besides, sub-lethal levels of these compounds results in a loss of insects? weight and change in protein content.Results showed the first step in the toxicity of free and microencapsulatedformulations of BHA and BHT against O. surinamensis and T. castaneum.